Occurrence, Distribution, and Ecological Risk Assessment of Antibiotics in Selected Urban Lakes of Hanoi, Vietnam - Hong Anh Duong; Thi Vi Phung; Thuy Ngoc Nguyen; Lan-Anh Phan Thi; Hung Viet Pham (Journal of Analytical Methods in Chemistry)
Residue concentrations of fifteen antibiotics including sulfonamides, quinolones, macrolides, β-lactams, and trimethoprim in lakes from Hanoi metropolitan area, Vietnam, were analyzed using ultra-performance liquid chromatography coupled with tandem mass spectrometry (UPLC/MS-MS) to elucidate their occurrence and behavior in urban environment. For surface water, the average concentrations of five antibiotic classes decreased in the order: sulfonamides (117.9 ng/L) > β-lactams (31.28 ng/L) > quinolones (20.19 ng/L) > macrolides (17.74 ng/L) > trimethoprim (8.93 ng/L). While the highest concentration of SMX was detected at 806.5 ng/L in surface water, those obtained in sediment were only at 1.35 ng/g because of their high solubility in water. Quinolones were found at a maximal concentration of 158.7 ng/L for OFL in water phase whereas those in sediment phase were 4,017 ng/g due to their great affinity in sediment. These findings revealed the different fate and release mechanisms of each antibiotic group in the environment. The ecological risk assessment implied some targeted compounds, and in particular, OFL and AZM could pose high risks to algae in the aquatic ecosystem.